Depositional Models of Deep-Water Gravity-Flow in Lacustrine Basin and Its Petroleum Geological Significance—A Case Study of Chang 6 Oil Group in Heshui Area, Ordos Basin, China - Yang, Yiming; Peng, Jun; Chen, Zhaobing; Zhou, Xiaoying; Zeng, Yao; Wang, Yubin; Wang, Xueying (Frontiers in Earth Science, 2022)
Due to its strong transporting energy, gravity-flow can carry huge amounts of sediments and organic matters from shallow water to deep lakes, directly or indirectly facilitating the formation of deep-water tight reservoirs and shale reservoirs. Therefore, it is necessary to study the genetic types, dynamic mechanisms, and sedimentary models of gravity-flow to facilitate the exploration of unconventional petroleum in large lacustrine basins. This research aims to study the genetic types, dynamic mechanisms, and sedimentary models of the gravity-flow of the Chang 6 oil reservoir group in the Heshui Area, Ordos Basin, China, so as to reveal its petroleum geological significance. Methods employed in this paper include field cross-sections and core observation, microscopic thin section identification, particle size analysis, and determination of rare earth elements. As a result, three types of gravity-flow are detected in the study area: slide-slump, sandy debris flow, and turbidity current. A certain slope gradient in bed form is required as a structural condition for the formation of a gravity flow, which determines its development level, distribution range, and flows transformation efficiency. Sufficient provenance serves as its material foundation, determining its sedimentary composition and development type. Earthquakes, volcanoes, and floods are the triggering forces; while fragmentation, liquefaction, and fluid mixing are the main dynamic mechanisms driving flow transformation. Two sedimentary models of gravity flow: slump turbidite body and sublacustrine fan, are distinguished based on the gravity-flow transformation relations, development mechanism, and spatial distribution law. The sandy debris flow in the middle fan braided channel microfacies of the sublacustrine fan sways the development of thick massive sand bodies in the study area. Hybrid event beds formed by the fluid transformation in a slump turbidite are the potential dessert area for deep-water tight oil and gas.